1914 building campaign tally sheet - Unknown:::Creator::::::::::::
Photograph shows a large tally sheet pinned to a wall. It is probably for the YWCA's 10 day building campaign started on June 2, 1914 and it runs the length of the wall shown in the photograph. The heading on the sheet reads: "Every day counts we count on you." The next line reads: "Executive committee. Womens. Mrs. John Richards. Young womens. Miss Florence Clayton. Citizens. Mr. Chas. Snyder. Young Mens. Dr. Bullitt. Business girls. M[rs]. J.W. Nixon. Normal. Washburn School. High School. Total." The far left column has dates that range from June 3, (1914?) to June 12, (1914?) and the following columns are filled with monetary amounts collected on those days by different groups.